Challenges in Emerging an Inclusive Learning Environment: A Case Study in an Elementary School - Widyhastuti; Karsono; Septi Yulisetiani (Universitas Pendidikan Ganesha, 2024)
Education is guaranteed by the state to ensure continuity and accessibility for all learners, aiming to provide equal educational opportunities for all students, including those with Special Needs (SN). Inclusive education is a crucial step toward achieving this goal. However, limitations in resources and community support often hinder its implementation in primary schools. The objective of this research is to elucidate how the principles of inclusion are applied in Elementary School. This study employs a qualitative approach and a case study methodology. Data were collected through the examination of inclusive support facilities, documentation of the Individual Learning Program (ILP), and interviews with teachers, parents of SN students, and Special Assistance Teachers (SAT). The interactive model developed by Miles & Huberman was utilized for data analysis to identify patterns, themes, and systemic solutions. The findings indicate that the school has implemented an inclusive program by modifying the curriculum, providing teacher training, and collaborating with the local community. Nevertheless, challenges such as a limited number of SATs, inadequate facilities, and a lack of community understanding remain significant obstacles. Ongoing training for teachers, enhancement of facilities, and raising awareness about the importance of inclusive education are solutions being implemented. This research demonstrates that systemic policies supporting community collaboration and capacity building within schools are essential for creating an inclusive and sustainable learning environment.